Staffordshire introduction - Thorn, Caroline; Thorn, Frank (The University of Hull)
The introduction discusses the history and assessment of the county; the county boundary; the administration of the county; the Hundreds, their reconstruction, rubrication, order, boundaries, and revised name-forms; Hundred courts, moot-sites, links with royal manors, and lordship; manorial and ecclesiastical organisation; the state of the manuscript for the county; its layout and content; writing and correction; places entered under the wrong Domesday county; duplicate entries; boroughs, castles and Forest; related or 'satellite' texts; the Burton Cartulary, the Burton survey, other Burton texts, and Hemming's Cartulary; the identification of places; the editorial history of earlier versions of the notes, and the current state of the revision. The introduction has been written for this edition by Caroline and Frank Thorn.